Pemberdayaan Masyarakat Tani Melalui Pemanfaatan Tumbuhan Lokal Sebagai Pengendali Hama Ramah Lingkungan di Desa Padengo Kecamatan Popayato Barat - Mohamad Lihawa; Anggry Pratama (Univeristas Negeri Gorontalo, 2019)
Pohuwato Regency is the largest maize producing area in Gorontalo Province. Since 2015, about 50 percent of maize production in Gorontalo Province has come from Pohuwato Regency. Padengo Village, West Popayato District is one area that contributes to producing maize in Pohuwato Regency because most of the farmers in this village are maize farmers. Depend on the field observations and interviews with farmers in Padengo village, it is known that one of the problems faced by corn farmers is the difficulty of controlling armyworm pests in corn. Based on these conditions, the thematic real work lecture program carries out community service on empowering farming communities through the use of local plants as environmentally friendly pest controllers. In this community service program, seminars and training on the manufacture of vegetable pesticides have been carried out for farmers, production of vegetable pesticides from siam weed leaves and gamal leaves, application of vegetable pesticides on demonstration plots as well as regular observations of maize pest populations on maize fields in Padengo village, West Popayato District.